The Effect of Counselling Interventions on Work Stress of Operational Level Employees in Apparel Industry - Karunarathna, D.I.M.; Subashini, B.L.C.; Weerasinghe, T.D. (University of Jaffna, 2018)
The current study was initiated to assess the effect of organizational counselling interventions on work stress of operational level employees in apparel, with the aim of bridging the gap in the context with empirical knowledge. Hence, this was conducted as a cross-sectional, quantitative field study among a sample of 87 operational level employees randomly selected from three (03) apparel manufacturing organizations in Sri Lanka. Primary data was collected via a standard questionnaire which met the acceptable level of validity and reliability. Descriptive statistics, Pearson correlation coefficient and simple regression were employed to analyze data. It is found that there is a significant negative, but the weak relationship (r = -0.233) between two constructs, and a significant, but the smaller impact of organizational counselling interventions on work stress of employees (r2 = 5.4%) in the apparel industry. Findings of the current study support the empirically justified conception that operational level workers are more ‘financial sensitive' and much more focus on physiological needs than psychological needs. Hence, it is recommended for practising managers in apparel to pay much attention to the factors other than organizational counselling, which could probably manipulate the unexplained variation of work stress of operational level employees.
Keywords: Organizational counselling; Work stress; Organizational counselling interventions; apparel industry